Penguatan Peran Warga Masyarakat dalam Perencanaan, Penganggaran, dan Evaluasi Hasil Pembangunan Desa - Susetiawan Susetiawan; DC Mulyono; Muhammad Yunan Roniardian (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2018)
Law No. 6 of 2014 mandates that village development planning should be implemented in a participatory manner, involving all communities including vulnerable groups (minorities, disabled, women, poor). It is so that the development undertaken by the village really beneficial to all villagers in the village. However, to date, most villages in Indonesia are still unable to implement the mandate. There are villages that carry out elitist development planning, fully undertaken by the village administration without the involvement of the community. There are also villages that have tried to involve the community, through musrenbangdes mechanism, but unfortunately not all community components are invited in the musrenbangdes. The impact of development planning that has not been participatory is that village development can not be felt by all levels of society. Meanwhile, village development can not be said to succeed if there are still some people who have not been able to feel the benefits. As one of the efforts to realize the participatory village development planning, PSPK UGM conducts training on planning, budgeting and evalauasi of village development results in Jomboran Village. The activity involves representatives from all components of the village community (community members, administrators of social organizations, and village government), and through this training it is hoped that in the future village development planning can be implemented in a participatory manner so that the results of the builders can be felt by all citizens.